Dihydrotanshinone I Attenuates Atherosclerosis in ApoE-Deficient Mice: Role of NOX4/NF-κB Mediated Lectin-Like Oxidized LDL Receptor-1 (LOX-1) of the Endothelium - Zhao, Wenwen; Li, Chunxia; Gao, Hongwei; Wu, Qin; Shi, Jingshan; Chen, Xiuping (Frontiers in Pharmacology, 2016)
Dihydrotanshinone I (DHT) is a natural compound extracted from Salvia miltiorrhiza Bunge which has been widely used for treating cardiovascular diseases. However, its role in atherosclerosis remains unclear. In this study, the effect of DHT on atherosclerosis were investigated using apolipoprotein E-deficient (ApoE-/-) mice and endothelial cells. In lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs), DHT (10 nM) decreased lectin-like ox-LDL receptor-1 (LOX-1) and NADPH oxidase 4 (NOX4) expression, reactive oxygen species (ROS) production, NF-κB nuclear translocation, ox-LDL endocytosis and monocytes adhesion. Silence NOX4 inhibited LPS-induced LOX-1 expression, NF-κB nuclear translocation, ox-LDL endocytosis and monocytes adhesion. In ApoE-/- mice fed with an atherogenic diet, DHT (10 and 25 mg kg−1) significantly attenuated atherosclerotic plaque formation, altered serum lipid profile, decreased oxidative stress and shrunk necrotic core areas. The enhanced expression of LOX-1, NOX4, and NF-κB in aorta was also dramatically inhibited by DHT. In conclusion, these results suggested that DHT showed anti-atherosclerotic activity through inhibition of LOX-1 mediated by NOX4/NF-κB signaling pathways both in vitro and in vivo. This finding suggested that DHT might be used as a potential vascular protective candidate for the treatment of atherosclerosis.